2020
DOI: 10.1111/jdv.16683
|View full text |Cite
|
Sign up to set email alerts
|

Practical recommendations for systemic treatment in psoriasis in case of coexisting inflammatory, neurologic, infectious or malignant disorders (BETA‐PSO: Belgian Evidence‐based Treatment Advice in Psoriasis; part 2)

Abstract: Background Psoriasis patients carry an increased risk for associated comorbidities. Dermatologists have to be aware of the effects of systemic treatments not only on psoriasis but also on co‐occurring diseases. In case of other coexisting inflammatory diseases, the right psoriasis treatment may improve both disorders. For infectious and malignant disorders, some treatments have to be avoided as they may be harmful. Objective The primary objective of this project was to collect evidence for the creation of prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 78 publications
0
26
0
Order By: Relevance
“…Comorbidities could influence the treatment strategy (14). Figure 2 lists selected therapeutics for adult systemic psoriasis with comorbidities (74)(75)(76)(77). Treatment should be tailored to meet the needs of patients (Figure 2).…”
Section: Therapy For Psoriasismentioning
confidence: 99%
“…Comorbidities could influence the treatment strategy (14). Figure 2 lists selected therapeutics for adult systemic psoriasis with comorbidities (74)(75)(76)(77). Treatment should be tailored to meet the needs of patients (Figure 2).…”
Section: Therapy For Psoriasismentioning
confidence: 99%
“…In fact, qualitative‐quantitative interactions between drugs and disease cannot be excluded, making any initiative of clinical appropriateness difficult. These considerations also highlight the need to introduce sperm cryopreservation procedures for AD patients 98,99 . Sperm preservation in liquid nitrogen is common practice in case of cancer, and it is recommended to patients before surgery or before starting each therapy potentially damaging, also transiently, the quality of semen 100 …”
Section: Discussionmentioning
confidence: 99%
“…The rates per 100 PY of patients with serious gastrointestinal adverse events in the pooled dataset were 0.80 for tildrakizumab 100 mg and 0.43 for tildrakizumab 200 mg, and thus infrequent. Recent expert recommendations have suggested that tildrakizumab can be considered effective and well tolerated in patients with inactive and active IBD, even if the evidence level is low [32].…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%